Multi-Stakeholder Collaboration in Stunting Mitigation Efforts: A Study in Mesuji Regency - Jasman, Andri; Kartika, Tina; Yulianto , Yulianto (International Journal Labs, 2025)
Objective: In the face of the demographic bonus, a healthy workforce and productive employment are essential. However, stunting poses a significant threat to achieving this potential. Therefore, multi-stakeholder collaboration is essential, involving governments, the private sector, academia, and society. This study explores the dynamics of collaborative governance in overcoming stunting in Mesuji Regency, along with the role of actors. Methods: Using Using a qualitative descriptive approach, data was collected through Focus Group Discussions (FGDs) and document analysis, involving 15 key informants.Results: Demonstrate that local governments act as facilitators, while other stakeholders contribute through resources and active participation. Effective interagency coordination, ongoing policy support, and active stakeholder engagement are key supporting factors. Conclusion: The handling of stunting in Mesuji Regency shows the importance of multi-stakeholder collaboration. The government plays the role of facilitator, while other actors are actively involved through resources and participation. Success is underpinned by effective coordination, sustainable policies, and the involvement of all parties.